Quantitative analysis of a complex metal carbide formed during furnace cooling of cast duplex stainless steel using EELS and EDS in the TEM - Surasak Kuimalee (2018)
In this work, a method to determine the atomic ratio of Mo and C within complex metal carbides using EELS in the TEM has been developed. The method is based on the determination of k-factors for given experimental conditions from the EEL spectra of Mo2C and MoO3 standards, which had been independently checked by XRD and EPMA. Factors affecting the kMo/C value of the Mo2C standard were also investigated and the value was shown to be insensitive to background subtraction window width but sensitive to prolonged irradiation and specimen thicknesses above a critical value. The method and k-factor obtained from the Mo2C standard was applied to spectra from a complex metal carbide precipitate formed during furnace cooling of a cast duplex stainless steel. Using EELS and EDS in the TEM, the composition was estimated to be (Cr1.52Fe2.33Mo1.25Ni0.17Si0.46)C, which is close to M6C stoichiometry, and the structure was confirmed by electron diffraction. © 2010 Elsevier Ltd.